Glioma Stem Cells and Their Microenvironments: Providers of Challenging Therapeutic Targets - Elena Codrici; Ana-Maria Enciu; Ionela-Daniela Popescu; Simona Mihai; Cristiana Tanase (Hindawi Limited, 2016)
Malignant gliomas are aggressive brain tumors with limited therapeutic options, possibly because of highly tumorigenic subpopulations of glioma stem cells. These cells require specific microenvironments to maintain their "stemness," described as perivascular and hypoxic niches. Each of those niches induces particular signatures in glioma stem cells (e.g., activation of Notch signaling, secretion of VEGF, bFGF, SDF1 for the vascular niche, activation of HIF2α, and metabolic reprogramming for hypoxic niche). Recently, accumulated knowledge on tumor-associated macrophages, possibly delineating a third niche, has underlined the role of immune cells in glioma progression, via specific chemoattractant factors and cytokines, such as macrophage-colony stimulation factor (M-CSF). The local or myeloid origin of this new component of glioma stem cells niche is yet to be determined. Such niches are being increasingly recognized as key regulators involved in multiple stages of disease progression, therapy resistance, immune-escaping, and distant metastasis, thereby substantially impacting the future development of frontline interventions in clinical oncology. This review focuses on the microenvironment impact on the glioma stem cell biology, emphasizing GSCs cross talk with hypoxic, perivascular, and immune niches and their potential use as targeted therapy.